The Extracted Pectin from Ambarella Fruit Peel (Spondias dulcis) as Biosorbent in Adsorption of Cu(II) Metal Ions - Trisna Kumala Sari; Elinda Fithriana; Indang Dewata; Desy Kurniawati; Romy Dwipa Yamesa Away (Jurnal Riset Kimia, 2023)
Heavy metals are known to seriously injure land plants and animals, including humans, as well as marine species when present in contaminated water. For the batch adsorption technique used in this study, Cu(II) ions were removed from an aqueous solution using an inexpensive  environmentally friendly adsorbent prepared from the extracted pectin of ambarella fruit peel. The functional groups of the extracted pectin were studied using Fourier Transform Infrared Spectroscopy (FT-IR). Operational conditions like pH, contact time, and initial adsorbate concentration were investigated. FTIR characterization showed that pectin was successfully extracted from ambarella fruit peel with the appearance of the peaks at 3331.36 cm-1, 2924.02 cm-1, 1727.38 cm-1, 1626.20 cm-1, 1329.31cm−1, 1232.43cm−1, 994.18 cm−1 and these peaks have similar characteristic with a commercial pectin. The maximum uptake of Cu(II) ions was obtained at a pH of 4, a contact time of 90 min, an initial metal concentration of 150 ppm. The extracted pectin has an adsorption capacity of 6.5860 mg/g for the removal of Cu(II) ions from aqueous solution under the optimum adsorption conditions. In addition, the data obtained from contacting the extracted pectin of ambarella fruit peel in Batang Arau River water showed an adsorption capacity of 0.0376 mg/g. Therefore, the pectin that was extracted from the peel of the ambarella fruit could be used to filter out Cu(II) ions from aqueous solutions.